Transnational Japan as history empire, migration, and social movements - Iacobelli, Pedro; Leary, Danton; Takahashi, Shinnosuke (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2016)
"This volume looks at the history of Japan from a transnational perspective. It brings to the fore the interconnectedness of Japan's history with the wider Asian-Pacific region and the world. This interconnectedness is examined in the volume through the themes of empire, migration, and social movements"
Machine generated contents note: -- Introduction: Framing Japan´s Historiography into the Transnational Approach -- 1. Regionalism or Imperialism: Japan's Options towards Protected Korea after the Russo-Japanese War, 1905-1910 -- 2. Pan-Asianism in the Wartime Writings of Japanese, Chinese and Korean Intellectuals in a Transnational Space at Kenkoku University in Japanese-Occupied Manchuria -- 3. The 'Siberian Internment' and the Transnational History of the Early Cold War Japan, 1945-56 -- 4. Colonialism and Migration: From the Landscapes of Toyohara -- 5. Migrations and the Formation of a Diverse Japanese Nation during the First Half of the Twentieth Century -- 6. Japanese Migration to Colonial Singapore, 1890-1920: the collision and collusion of statehood and gender -- 7. A Language for Asia? Transnational Encounters in the Japanese Esperanto Movement, 1906-1928 -- 8. Imagining 'World Peace': The Anti-Nuclear Bomb Movement in Postwar Japan as a Transnational Movement -- 9. Transnationalism and Transition in the Ryukyus.
Includes bibliographical references (pages 243-263) and index.
Keywords: Transnationalism -- History -- 20th century; Imperialism -- History -- 20th century. -- Japan; Social movements -- History -- 20th century. -- Japan; Japan -- History -- Historiography. -- 20th century; Japan -- Foreign relations -- 20th century; Japan -- Foreign relations -- Asia; Asia -- Foreign relations -- Japan; Japan -- Emigration and immigration -- History -- 20th century